Modeling Customer Service Delivery in Banks Using Queuing Theory. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Efficient customer service delivery in banking operations is critical for maintaining customer satisfaction and resource utilization. Queuing theory is an approach to analyzing waiting lines, it provides a robust framework for modeling and improving service delivery in banks. This research explores the application of queuing theory to model customer service delivery processes in banks, focusing on service efficiency, customer wait times, and resource allocation. The data for this research was taken for a period of four weeks, covering all work days from Mondays to Fridays and hours from 8am to 4pm. The data analysis was done with the aid of EXCEL package for descriptive statistics and TORA for optimization system. From the performance measures researched, it shows that increasing the teller points to 3 would reduce the waiting time in the queue and system to 0.01481hours (53.32 seconds) and 0.05829hours (3.50 minutes) respectively as against the present situation where each customer has to wait in the queue and system for 0.30095hours (18.06 minutes) and 0,34443hours (20.67 minutes) respectively. This will result to each teller being busy for 62.3% of the time while remaining idle for 37.7% of the time.